The indirect health effects of malaria estimated from health advantages of the sickle cell trait - Sophie Uyoga (Nature Portfolio, 2019)
Estimates of the burden of malaria often don't take wider, indirect effects on overall health into consideration. Here, Uyoga et al. estimate the indirect impact of malaria on children’s health in a case-control study, using the sickle cell trait as a proxy indicator for an effective intervention.